Childhood Obesity and its Impact on Kidney Status - Salimovna, Goyibova Nargiza (Journal of Science in Medicine and Life, 2024)
Overweight and obesity are the most actual problems nowadays. Number of overweight patients steadily raises and duplicates every three decades. Obesity is associated with some factors of cardiovascular risk like diabetes mellitus and arterial hypertension, frequently leads to kidney disfunction. Obesity itself can result in poor renal hemodynamics, well-known risk factor of kidney dis-ease. We studied impact of overweight and obesity in children and adolescents on renal tubular function and glomerular filtration rаte.